HUBUNGAN KEMAMPUAN INKUIRI TERHADAP PEMAHAMAN KONSEP CALON GURU BIOLOGI PADA PEMBELAJARAN INKUIRI TERINTEGRASI NILAI KARAKTER - Dasrieny Pratiwi; Agil Lepiyanto (Bioedukasi: Jurnal Pendidikan Biologi FKIP UM Metro, 2018)
This study aims to understand the relationship of inquiry skills with conceptual understanding. This research is a correlational research. The result of analysis with regression test using SPSS found that the amount of contribution of inquiry ability to understanding student concept is 68,85%. and correlation value R = 0,830. This means a strong relationship between the ability to understand the concept of mercury with the students. Based on the results of hypothesis testing, obtained F value of 128.107 with a significance value of 0.000 <0.05 which means there is a relationship between cognitive ability and understanding of student concepts on the application of inquiry learning integrated character values. Kata kunci: kemampuan inkuiri, pemahaman konsep